Software Design of Transformer Terminal Unit - 贾志诚 (Kongzhi Yu Xinxi Jishu)
It introduces a kind of software structure for transformer terminal unit(TTU), describes the design of file system which includes operating system, database, communication interface and its main application programs, shows some important program sections.